Analysis of sediment from an irrigation dam in an agricultural valley impacted by the mega-drought in central Chile - Jaque, Jennery; Melo Pinochet, Naveska; Aránguiz-Acuña, Adriana; Pizarro, Héctor (Frontiers in Ecology and Evolution, 2023)
Central Chile is affected since 2010 by an increasing mega-drought accompanied by historically low precipitation rate, as a probable consequence of climate change. Additionally, increasing pressure exerted by the withdrawals of human activities such as agriculture and metal-mining promotes conditions for hydric scarcity. Despite this intensive use of the watersheds, and the sustained and increasing aridity, it has not been explored if an artificial sedimentary record can trace this changes in the agricultural valleys of the region. To unravel and evaluate the recent environmental/climatic variability, the effects of the mega-drought of the last 12 years and extractivist pressure on a Mediterranean valley of Central Chile, sediment records were obtained from an irrigation dam and studied through a multi-proxy analysis. The dam has been built and in operation since 1975 and is located in the Aconcagua River Valley, Valparaíso, Chile. Magnetic properties, carbon content, mineral composition and metals content were analyzed from a sediment 120 cm long core. Changes in vegetation cover from 1990 to 2020 were analyzed through NDVI filters. Horizons associated to drier conditions in the upper zone of the core were observed, which corresponded to the year 2001 to the present, assuming a constant sedimentation rate of 2.72 cm·yr-1. Additionally, the characteristic alternation of dry-wet conditions was observed in the deep horizon of the dam sediments. Concentrations of Cu, Pb, Al and As have increased over the years, while the Mo concentration decreased. Some of these elements are associated with copper mining existing in the valley. Analysis of Landsat images from the year 2000 to the present identified a significant decrease in vegetation cover associated with dry/wet periods, which could be related to cycles of El Niño/La Niña events. Although not all the proxies analyzed were sensitive to detect changes at the desired resolution since the dam is very recent, the results shed light on the effects of the interaction between industrial activities and decrease of water availability in multiple-use watersheds suggesting variations in metals concentrations and changes in water availability, probably promoted by anthropic activities, climatic events and increasing aridity in the Aconcagua River Valley.